Late presentation of esophageal cancer: Observations in a multiracial South-East Asian population - Abdullah, M.; Karim, A.A.; Goh, K.L. (Wiley-Blackwell, 2010)
OBJECTIVE: Esophageal cancer (ECA) is an important cancer in Malaysia. The aim of the study is to review the demographic data and clinical presentation of patients with ECA seen at the University of Malaya Medical Centre, Kuala Lumpur. METHODS: Patients with histologically proven ECA were recruited for the study. Patients' case notes, endoscopy and operating theater records were reviewed. All cases were histologically confirmed. RESULTS: A total of 143 patients with ECA was diagnosed between 1998 and 2003. The mean age of the patients was 63.1 +/- 12.1 years with a male : female ratio of 1.8:1. Of these 50.3 percent were Indians, 32.9 percent, Chinese and 16.8 percent Malays. The overall hospital-based prevalence rates per 100 000 admissions according to races were: Malay; 23.5, Chinese; 57.4 and Indian; 134.1. The location of the tumors was: upper; 16 (11.2%) middle; 52 (36.4%) and lower; 75 (52.4%). The histological type of ECA were: squamous cell carcinomas; 113 (79.0%) and adenocarcinomas; 30 (21.0%). The ECA stage at diagnosis, was: II; 18 (12.6%), III; 23 (16.1%) and IV; 102 (71.3%). Only 24 (16.8%) patients underwent surgery and13 (9.1%) were considered curative. Overall 114 (79.7%) patients underwent palliative endoscopic stenting and six (4.2%) were given other palliative therapy including radiotherapy. CONCLUSIONS: Squamous cell cancer was the predominant type. ECA presents late in our patients and only a minority of patients underwent curative surgery.